Pengaruh Jarak Tanam dan Pemangkasan Daun Terhadap Peroduktivitas Tanaman Terung Ungu (Solanum melongena L.) - Deddy Wahyudin Purba; Lokot Ridwan Batubara; Satria Pramuja Ramadhan; Oktoni Eryanto (UNIVERSITAS LABUHANBATU, 2026)
The study used a Factorial Randomized Block Design (RAK) consisting of 2 treatment factors. The first was the effect of planting distance (J) consisting of 3 treatment levels, namely J1 = planting distance 60 x 60 cm, J2 = planting distance 60 x 70 cm, J3 = planting distance 70 x 80 cm. The second was leaf pruning (D) consisting of 4 treatment levels, namely D0 = no pruning, D1 = pruning at 28 DAS, D2 = pruning at 35 DAS, D3 = pruning at 42 DAS. Based on observational results, the influence of planting distance in treatment J2 produced the best plant height, leaf area, and fruit weight per plot with results of 46.31 cm, 85.44 cm², and 2.90 kg, respectively; treatment J3 produced the best stem diameter of 4.63 mm; treatment J1 produced the best number of leaves and fruit per sample with results of 22.33 leaves and 7.83 fruits. Leaf pruning in treatment D2 produced a plant height of 44.30 cm; treatment D3 produced the best stem diameter of 4.63 mm; treatment D1 produced the best number of leaves of 23.11 leaves; treatment D0 produced the best leaf area, number of fruits per sample, and fruit weight per plot with results of 84.88 cm², 8.11 fruits, and 2.80 kg. The interaction effect of planting distance and leaf pruning showed no significant difference in all observed parameters. Keywords: planting distance, pruning, eggplant, productivity